The relationship between energy cost of turn movements and running speeds - Hatamoto, Y.; Yamada, Y.; Sagayama, H.; Ueno, S.; Ichikawa, M.; Higaki, Y.; Kiyonaga, A.; Tanaka, H. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
When evaluating the energetic demands of a ball game, both the distance covered as well as the energy cost of other movements (e.g. jumping, dribbling and tackling) should be considered. Bloomfield et al. (2007) reported an average of 700 changes of direction ("turn movement") per match in English Premier League soccer, and Bradley et al. (2009) found that soccer players performed high intensity running (>14 km/h) more than 250 times in a match. Extra energy is expended during a turn movement because of the extra muscle activity involved. However, there is limited research on the physiological demands of turn movements. We developed the "Different Frequency Accumulation Method: (DFAM)" for evaluating the instantaneous physiological demands of turn movements during running. The purpose of the present study was to measure the physiological demands of turn movements at different running speeds using the DFAM. Methods Eight healthy young men (aged 18-22 years) participated in the study. Five trials were performed where the subjects were required to run at different speeds (3, 4, 5, 6, and 7 km/h). Each trial included four incremental stages of turn frequency (13, 18, 24 and 30 per minute), with each stage lasting 3 minutes. Each trial required the subject to run along a line and perform 180° turn movements at the required speed and turn frequency. The oxygen consumption during the trial was determined using respiratory gas analysis. The oxygen consumption of a turn at each speed was calculated from the slope of the regression for oxygen consumption against the turn frequencies using the DFAM. Heart rate (HR), post-trial blood lactate, and ratings of perceived exertion (RPE) were also measured. Results: The oxygen consumption values, for a turn movement at 3, 4, 5, 6 and 7 km/h, were 0.26 ± 0.04, 0.35 ± 0.05, 0.46 ± 0.11, 0.68 ± 0.09, and 0.89 ± 0.13 ml/kg/min, respectively. ANOVA revealed that the oxygen consumption of a turn movement increased as the running speed increased (P < 0.001). HR, blood lactate and RPE increased with each running speed and increase in turn frequency. Conclusion: We suggested the equation describing the relationship between running speeds and the oxygen consumption of a turn movement would be in accordance with the well-known formula for kinetic energy, E = 1/2 mv2, where m is the body mass and v is the speed, with the oxygen consumption of a turn movement possibly proportional to v2. This information could possibly be used for estimating the energy cost of a ball game.